Benefit risk considerations for African swine fever virus live attenuated vaccines - Sandra Blome; Virginia Friedrichs; Alexander Schäfer; Martin Beer (npj Vaccines)
In response to the recent publication on safety concerns related to “ASFV-G-∆I177L” by van den Born et al. (2025), we emphasize the need for a thorough, context-specific risk assessment before drawing conclusions about the general field use of the ASFV-G-∆I177L vaccine strain. While valid safety concerns were raised, historical precedents highlight that potential risks, including reversion or recombination, can be managed effectively within structured vaccination strategies.